Cullin 7 and Fbxw 8 expression in trophoblastic cells is regulated via oxygen tension: Implications for intrauterine growth restriction - Fahlbusch, Fabian; Dawood, Yousif Louay; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Tzschoppe, Anja; Schneider, Holm; Strissel, Pamela; Beckmann, Matthias; Schleussner, Ekkehard; Rübner, Matthias; Dörr, Helmuth-Günther; et al. (Journal of Maternal-Fetal & Neonatal Medicine, 2012)
Objective: The F-box protein Fbxw8 is a cofactor of Cullin 7 (Cul7), which regulates protein transfer to the proteasome and cell growth. Cul7 or Fbxw8 deficiency is associated with intrauterine growth restriction (IUGR) due to abnormal placental development leading to poor oxygen supply to the fetus. We studied the role of hypoxia for Fbxw8 and Cul7 expression in trophoblastic cells. Methods: Immunomagnetic bead-separated extravillous trophoblast (EVT) and villous trophoblast (VT) and trophoblast cell lines were incubated with 1 or 8% O2. Fbxw8 and Cul7 expression was determined in IUGR versus matched control placentas. Results: Fbxw8 was expressed uniformly in trophoblasts, whereas Cul7 expression was most prominent in trophoblast cell lines. Hypoxia reduced expression of Cul7 and Fbxw8 in all trophoblastic cells, except for villous trophoblasts. In vivo, Cul7 and Fbxw8 were detected in syncytiotrophoblast cells, VT, and EVT cells. Although no significant changes in expression levels of Fbxw8 or Cul7 were noted in IUGR compared with control placentas, Fbxw8 expression correlated negatively with gestational age in the control, but not in the IUGR group. Conclusion: Fbxw8 and Cul7 expression reveals a complex regulation in trophoblastic cells. Our findings suggest that dysregulation of Cul7 and Fbxw8 expression might affect trophoblast turnover in IUGR. © 2012 Informa UK, Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Cul7; Fbxw8; IUGR; Oxygen; Placenta; Trophoblast